Peningkatan Kompetensi Profesional Guru melalui Penelitian Tindakan Kelas - Muhammad Nafi Annury (LP2M of Institute for Research and Community Services - UIN Walisongo, 2018)
This paper evokes efforts to increase teacher competency in the madrasa through classroom action research. In delivering knowledge, not only can it be done in the classroom, but it can also be done outside the classroom. Scientific work is also a professional value of a teacher, because the activity of writing scientific work supports the teaching profession, both in the learning and teaching process or in discussing to solve certain problems proposed. The problems identified in this community service program are: the teachers' knowledge and understanding of Classroom Action Research is still lacking, the teacher's experience in classroom action research is still lacking, the experience of preparing proposals is still lacking, and culture in research activities in the school environment is still lacking. The results obtained through this activity are there is an increase in the understanding of subject teachers in the implementation of Classroom Action Research, an increase in the ability of subject teachers in preparing proposals for Classroom Action Research at SMPIT Assalamah Ungaran and an increase in the ability of subject teachers in conducting Classroom Action Research. Tulisan ini mengunkap upaya peningkatan kompetensi guru di madrasah melalui penelitian tindakan kelas. Karya tulis ilmiah tidak hanya dapat dinikmati oleh peserta didik, tetapi juga oleh masyarakat luas. Karya ilmiah juga merupakan nilai profesionalisme dari seorang guru, karena kegiatan menulis karya ilmiah mendukung profesi guru, baik dalam proses belajar dan mengajar ataupun dalam berdiskusi untuk memecahkan masalah tertentu yang diajukan. Permasalahan yang diidentifkasi pada program pengabdian kepada masyarakat ini adalah: pengetahuan dan pemahaman para guru tentang Penelitian Tindakan Kelas masih kurang, pengalaman guru dalam hal penelitian tindakan kelas masih kurang, pengalaman menyusun proposal masih kurang, dan budaya dalam hal kegiatan penelitian di lingkungan sekolah masih kurang. Hasil yang diperoleh melalui kegiatan ini yaitu terdapat peningkatan pemahaman para guru mapel disekolah dalam pelaksanaan Penelitian Tindakan Kelas, peningkatan kemampuan para guru mapel dalam menyusun proposal Penelitian Tindakan Kelas di SMPIT Assalamah Ungaran dan terdapat peningkatan kemampuan para guru mapel dalam melaksanakan Penelitian Tindakan Kelas.